A holistic framework for the study of interdependence between electricity and gas sectors. (November 2016) - Peng, Donna; Poudineh, Rahmatallah
Abstract: The increasing global use of natural gas for power generation has begun a period of interdependence between two important energy industries. Understanding of the extended gas-to-power supply chain is important for power and gas system operators, integrated utilities, regulators, and government bodies responsible for overall energy policy. This paper seeks to align the study of gas and power industries by providing a holistic framework for the thorough identification and discussion of power and gas sector structure, infrastructure, market, and regulatory drivers. Additionally, it offers a simulation model as an example of applying the analytical framework to study gas and power interdependence in the UK. Highlights: This paper proposes a framework to align the study of gas and power industries. Through the lens of framework gas-to-power interdependence can be identified. We provide an example of applying the framework to case of the UK.